RB-SR ISOTOPIC ANALYSIS OF FLUID INCLUSIONS IN QUARTZ: EVALUATION OF BULK EXTRACTION PROCEDURES AND GEOCHRONOMETER SYSTEMATICS USING SYNTHETIC FLUID INCLUSIONS - Pettke T.; Diamond L.W. (My University, 1995)
Analysis of Rb-Sr isotopic and elemental signatures of fluid inclusions is technically demanding, but it offers enormous potential in elucidating the timing, sources, and geochemical reaction paths of fluids in the Crust. Fluid inclusions of known isotopic and elemental ratios have been synthesized in quartz to serve as control samples. With these standards, two previously used fluid extraction procedures for bulk quartz samples have been evaluated and improved: crushing in a mortar followed by leaching and thermal decrepitation followed by leaching.Our experiments on quartz show that 87Sr86Sr analysis is straightforward using both methods, regardless of the leaching solution employed. However, analysis of accurate 87Rb86Sr ratios is not trivial. Leaching with pure water is only 93% efficient and yields elevated ratios owing to failure to inhibit surface adsorption of Sr. Leaching with a La3+ -doped acid solution solves this problem; it is 99.7% efficient and yields accurate ratios. Crushing is the only fluid liberation method which delivers the correct 87Rb86Sr values. In contrast, thermal decrepitation yields 87Rb86Sr ratios which are quite reproducible, but exclusively incorrect. If inert sample containers are used, falsely elevated ratios are obtained at all decrepitation temperatures due to three concurrent extraction artefacts. However, if silica glass tubes are used, reaction of Rb with the glass at temperatures above #500°C falsely lowers the 87Rb86Sr signatures. We, therefore, suspect all published isotopic analyses of fluid inclusions obtained by thermal decrepitation to be in error.The trace contents of Rb and Sr in the host quartz crystals are measurable and have markedly differentRb ratios compared to the hydrothermal parent fluid. Thus analyses of leachates and host-mineral residues by the crushing method allow accurate ages to be calculated with certainties of an order which are useful for geochronology. Since fluid extraction levels vary between samples, the residues define an array on an isochron diagram, whereas the leachates define a unique point. These systematic characteristics explain hitherto poorly understood analyses in the literature. Because they represent mixing-lines, such isochrons carry only the significance of two-point ages which require independent verification of constant initial 87Sr86Sr. Thus their ultimate relevance to geology hinges on whether the analysed fluid inclusions can be identified petrographically as being primary.